The Influence of Learning Management System Management on Islamic Character Development in Madrasahs - Nabrisi Rohid; Siti Masitoh; Fajar Arianto; Lutfi Isni Badiah; Nibrosu Rohid (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the influence of Learning Management System (LMS) management on learning outcomes and Islamic character development among students of Madrasah Aliyah through an explanatory quantitative research design. The study conceptualises Islamic character development not as a subject-specific religious outcome, but as an institutional and managerial outcome of systematically managed digital learning environments. LMS management is operationalised as the structured use of digital platforms to support planning, implementation, monitoring, and evaluation of learning processes within madrasahs. The research analyses the relationship between LMS usage and two key dependent variables: cognitive learning outcomes and Islamic character development, encompassing honesty, discipline, responsibility, digital ethics, and empathy. Data were collected using a structured Likert-scale questionnaire administered to 120 students who had been actively using the LMS for at least 1 academic semester. The collected data were analysed using multiple regression techniques to examine the magnitude and significance of the relationships between variables. The results indicate that LMS management has a statistically significant and positive influence on both learning outcomes and Islamic character development. The effect of LMS management on learning outcomes was found to be stronger (β = 0.562, p < 0.01) than its effect on Islamic character development (β = 0.494, p < 0.01), suggesting that LMS is more effective in supporting cognitive achievement than in fostering character development. Further analysis shows that LMS usage explains 41.6% of the variance in students’ learning outcomes and 36.5% of the variance in Islamic character development. Despite these positive findings, the study reveals that the integration of Islamic values into LMS platforms remains limited, with only 50% of the surveyed madrasahs reporting the effective implementation of Islamic value-based digital learning content. This limitation indicates that character development through LMS has not yet been systematically planned or institutionally governed, but remains largely incidental. The findings highlight the need for stronger pedagogical planning, institutional coordination, and strategic content development to optimise the LMS's role in supporting holistic student development.